2015
DOI: 10.1007/s10661-015-4290-3
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental management practices in the Lebanese pharmaceutical industries: implementation strategies and challenges

Abstract: This research attempts to provide an understanding of the Lebanese pharmaceutical industries' environmental management strategies, priorities, and perceptions as well as drivers, barriers, and incentives regarding the implementation of the voluntary ISO 14001 Environmental Management System. Accordingly, a semistructured in-depth interview was conducted with the pharmaceutical industries. The findings revealed a significant lack of knowledge about the standard among the industries. The main perceived drivers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…According to Walker, Di Sisto and McBain (2008), barriers to environmental management tend to vary according to the organisational context, and thus, in line with the above objectives, a survey was conducted with ISO 9001-certified manufacturing companies located in Brazil. According to Massoud et al (2015), companies with ISO 9001 tend to be more motivated to adopt environmental management initiatives. Terziovski, Power and Sohal (2003) found that organisations that pursue ISO 9001 certification are more likely to report improved organisational performance.…”
Section: Introductionmentioning
confidence: 99%
“…According to Walker, Di Sisto and McBain (2008), barriers to environmental management tend to vary according to the organisational context, and thus, in line with the above objectives, a survey was conducted with ISO 9001-certified manufacturing companies located in Brazil. According to Massoud et al (2015), companies with ISO 9001 tend to be more motivated to adopt environmental management initiatives. Terziovski, Power and Sohal (2003) found that organisations that pursue ISO 9001 certification are more likely to report improved organisational performance.…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth review of the literature allowed us to identify the main motivational factors that drive organizations to implement ISO 14001, which are related to environmental regulations, the market, and/or the pursuit of better economic and environmental performance [5,[27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lastly, the literature review also suggests, albeit inconclusively, that market-related factors can act as a major motivational force in the adoption of the standard [77], giving companies a competitive edge [78,79] in both internal and external markets through the drive to improve customer satisfaction [8] and the image and reputation of the organization [6,32,34,38,43,71,80], as well as the agri-food sector as a whole [24,29].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations